Quantum dot-loaded monofunctionalized DNA Icosahedra for single particle tracking of endocytic pathways - Bhatia, Dhiraj (Nat Nanotechnol, 2016)
Functionalization of quantum dots (QDs) with a single biomolecular tag using traditional approaches in bulk solution has met with limited success. DNA polyhedra consist of an internal void bounded by a well-defined three-dimensional structured surface. The void can house cargo and the surface can be functionalized with stoichiometric and spatial precision. Here, we show that monofunctionalized QDs can be achieved by encapsulating QDs inside DNA icosahedra and functionalizing the DNA shell with an endocytic ligand. We deployed the DNA-encapsulated QDs for real time imaging of three different endocytic ligands - folic acid, galectin-3 (Gal3) and the Shiga toxin B-subunit (STxB). Single particle tracking of Gal3 or STxB-functionalized, QD-loaded DNA icosahedra allows us to monitor compartmental dynamics along endocytic pathways. These DNA-encapsulated QDs that bear a unique stoichiometry of endocytic ligands represent a new class of molecular probes for quantitative imaging of endocytic receptor dynamics.